2017
DOI: 10.3892/etm.2017.5446
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside attenuates hypoxia/reoxygenation‑induced human brain vascular smooth muscle cell injury by activating the SIRT1/FOXO3α pathway

Abstract: It has been reported that salidroside (SAL), a natural dietary isothiocyanate, exhibits neuroprotective roles in cerebral ischemia-reperfusion injury. However, to the best of our knowledge, its underlying protective mechanism remains unknown. Sirtuin 1 (SIRT1) is a class III histone deacetylase involved in a variety of cellular functions. SIRT1 has been identified as a mediator of cerebral ischemia and may induce neuroprotection by activating various intracellular downstream targets, such as forkhead box prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Studies demonstrated that FOXO3 functionally interacted with the PI3K/AKT signalling pathway to regulate the proliferation of smooth muscle cells . In addition, activation of FOXO3 contribute to the protective effects of salidroside on hypoxia/reoxygenation‐induced human brain vascular smooth muscle cell injury . FOXO3 was down‐regulated in the fibroblasts isolated from PAH calves and patients with idiopathic PAH and functioned as an important mediator in the miR‐124‐mediated proliferation of pulmonary vascular fibroblasts, suggesting the potential role of FOXO3 in the pathophysiology of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that FOXO3 functionally interacted with the PI3K/AKT signalling pathway to regulate the proliferation of smooth muscle cells . In addition, activation of FOXO3 contribute to the protective effects of salidroside on hypoxia/reoxygenation‐induced human brain vascular smooth muscle cell injury . FOXO3 was down‐regulated in the fibroblasts isolated from PAH calves and patients with idiopathic PAH and functioned as an important mediator in the miR‐124‐mediated proliferation of pulmonary vascular fibroblasts, suggesting the potential role of FOXO3 in the pathophysiology of PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, resveratrol modulates the activity of SIRT3 and SIRT5 ( Dai et al, 2018 ). Several other natural extracts also activate SIRT1, including magnolol ( Kou et al, 2017 ), oxymatrine ( Zhou et al, 2018 ), curcumin ( Miao et al, 2016 ), salvianolic acid B ( Lv et al, 2015 ), arctigenin ( Zhang S. et al, 2017 ), astaxanthin ( Zhang et al, 2019 ), salidroside ( Xu et al, 2018 ), ginsenoside ( Cheng et al, 2019 ), icariin ( Zhu et al, 2010 ), low molecular weight fucoidan ( Wang et al, 2016 ), and saponin from Aralia taibaiensis ( Duan et al, 2019 ). These findings suggest that Chinese traditional medicine may be a source of sirtuin modulators.…”
Section: Sirtuins As Promising Therapeutic Targetsmentioning
confidence: 99%
“…Therefore, salidroside elevates ATGL expression and then generates more ligands for PPARα to inhibit cardiac hypertrophy. Salidroside can affect the function of some protein factors such as sirt1, FOXOs and AMPK ( Lan et al, 2017 ; Xu et al, 2018 ; Li et al, 2019 ). Salidroside elevated the protein expressions of SIRT1 and phosphorylated FOXO3α and then attenuated the injury of human brain vascular smooth muscle cells induced by the hypoxia/reoxygenation treatment ( Xu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salidroside can affect the function of some protein factors such as sirt1, FOXOs and AMPK ( Lan et al, 2017 ; Xu et al, 2018 ; Li et al, 2019 ). Salidroside elevated the protein expressions of SIRT1 and phosphorylated FOXO3α and then attenuated the injury of human brain vascular smooth muscle cells induced by the hypoxia/reoxygenation treatment ( Xu et al, 2018 ). In colitis mice, the expressions of SIRT1, FOXO1, FOXO3α, and FOXO4 could be increased by salidroside to attenuate inflammation reaction ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%